'Midas, transmuting all, into paper': the Bank of England and the Banque de France during the Napoleonic Wars - Jagjit S. Chadha; Elisa Newby (University of Kent, School of Economics, 2013)
This paper assesses Revolutionary and Napoleonic wartime economic policy. Suspension of gold convertibility in 1797 allowed the Bank of England to nurture British monetary orthodoxy. The Order of the Privy Council suspended gold payments on Bank of England notes and afforded simultaneous protection to the government and the Bank in pursuit of the conflicting goals of price stability and war finance. The government, the Bank of England and the commercial banks formed a loose alliance drawing on due political and legal processes and also paid close attention to public opinion. We suggest that the ongoing solvency of the Bank of England was facilitated by suspension and allowed the Bank to continue to make substantial profits throughout the Wars. It became acceptable for merchants to continue to trade with non-convertible Bank of England notes and for the government to finance the war effort, even with significant recourse to unfunded debt. These aspects combined to create a suspension of convertibility that did not undermine the currency. By contrast, the Assignats debacle had cost the French monetary system its reputation in the last decade of the 18th century and so Napoleonic finance had to evolve within a more rigid and limiting framework.
Keywords: C61; E31; E4; E5; N13; 330; Monetary Orthodoxy; Suspension of Convertibility; War Finance